2019
DOI: 10.1016/j.ejro.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of diffusion tensor imaging in identification of degenerative cervical spondylotic myelopathy

Abstract: Aim and objectivesTo study the diagnostic accuracy of Diffusion tensor imaging technique in detection of cervical spondylotic myelopathy changes.Material and methodStudy population included 50 patients with symptoms of cervical myelopathy. The patients were evaluated based on symptoms using the European myelopathy scoring system and were divided into: Grade 1, including patients with mild symptoms; Grade 2, referring to patients with moderate symptoms and Grade 3, which included patients revealing severe sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 12 publications
5
10
0
Order By: Relevance
“…The proposed cut-off for the FA value was lower (0.46), and the ADC value was higher (1.29) at C5–C6 level, the level that was affected the most (53.8%) in our study. Similar results were reported by Nukala et al [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…The proposed cut-off for the FA value was lower (0.46), and the ADC value was higher (1.29) at C5–C6 level, the level that was affected the most (53.8%) in our study. Similar results were reported by Nukala et al [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed that DTI is 93% more sensitive in detecting early myelopathic changes than the conventional MRI. These results are consistent with Facon et al [2], Kara et al [4], Yoo et al [6], Banaszek et al [8] and Nukala et al [9].…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study show that ADC values at C1 level are significantly higher in patients with the anterior atlanto-axial instability than in patients without instability. These results are consistent with studies concerning diffusion parameters in patients with cervical degenerative myelopathy: The researchers described higher ADC values in patients with spinal canal stenosis in comparison with the control group [12][13][14][15][16], as well as higher ADC values in the area of spinal canal stenosis than in other parts of the spinal cord [17,18]. The high diffusion coefficient at the site of the spinal cord injury can be explained by mechanical cell damage caused by repeated pressure of the vertebrae (especially the dens) on the cord.…”
Section: Discussionsupporting
confidence: 89%